Effectiveness of Water Hyacinth (Eichhornia crassipes) and Water Lettuce (Pistia stratiotes) in Improving Tofu Wastewater Quality through Phytoremediation - wardatul hidayah (Journal of Creative Power and Ambition (JCPA), 2026)
Tofu wastewater contains high concentrations of organic matter, suspended solids, and dissolved solids that may deteriorate water quality if discharged directly into the environment. Phytoremediation is an environmentally friendly wastewater treatment method that utilizes aquatic plants to improve water quality. This study aimed to evaluate the effectiveness of water hyacinth (Eichhornia crassipes) and water lettuce (Pistia stratiotes) as phytoremediation agents for tofu wastewater treatment. The experiment was conducted using four treatments, namely control (P0), water hyacinth (P1), water hyacinth + water lettuce (P2), and water lettuce (P3). Observations were carried out on days 0, 7, 14, and 21. Water quality parameters analyzed included pH, temperature, Dissolved Oxygen (DO), Total Dissolved Solids (TDS), and Total Suspended Solids (TSS). The results showed that phytoremediation for 21 days altered the quality of tofu wastewater. The pH values generally increased from acidic conditions toward more neutral conditions, while temperature remained relatively stable throughout the observation period. Water lettuce was more effective in stabilizing pH and reducing TSS, whereas water hyacinth showed better performance in maintaining DO concentrations and controlling TDS accumulation. These findings indicate that both plant species have potential as phytoremediation agents for tofu wastewater treatment, with their effectiveness depending on the targeted water quality parameters.